Maternal high-fat diet during pregnancy with concurrent phthalate exposure leads to abnormal placentation - Athilakshmi Kannan (Nature Portfolio, 2021)
Abstract Di(2-ethylhexyl) phthalate (DEHP) is a synthetic chemical commonly used for its plasticizing capabilities. Because of the extensive production and use of DEHP, humans are exposed to this chemical daily. Diet is a significant exposure pathway and fatty food contain the highest level of phthalates. The impact on pregnancy following DEHP exposure and the associated interaction of high fat (HF) diet remains unknown. Here we report that exposure of pregnant mice to an environmentally relevant level of DEHP did not affect pregnancy. In contrast, mice fed a HF diet during gestation and exposed to the same level of DEHP display marked impairment in placental development, resulting in poor pregnancy outcomes. Our study further reveals that DEHP exposure combined with a HF diet interfere with the signaling pathway controlled by nuclear receptor PPARγ to adversely affect differentiation of trophoblast cells, leading to compromised vascularization and glucose transport in the placenta. Collectively, these findings demonstrate that maternal diet during pregnancy is a critical factor that determines whether exposure to an environmental toxicant results in impaired placental and fetal development, causing intrauterine growth restriction, fetal morbidity, and mortality.